Role and Significance of Marketplaces in a Large Town – the Example of Łódź in Poland - Kulawiak, Anita (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2020)
Currently, the further functioning of marketplaces in towns is in question. This is related to both the intensive development of large -scale trade, displacing this traditional form of trade, and the appropriation of this space by the town authorities for other, non -commercial purposes. At the same time, however, for many inhabitants marketplaces still play an important role, mainly as a place to shop every day. In the context of observed research inaccuracies, the article deals with the problem of identifying the role of marketplaces in a modern town. The theoretical and methodological basis of the undertaken research is the concept of the function of a place of A. Suliborski (2001). Using said concept allowed for investigating the utility and social role of marketplaces. The article uses various research methods: study and field methods including a questionnaire interview that was carried out on a group of 200 Łódź residents.